Avaliação neuropsicofarmacológica dos mecanismos CRFérgicos na amídala, nas reações de defesa de camundongos pré-expostos à derrota social - Cipriano, Ana Cláudia (2015)
Stressful situations are a real or potential threat for psychological or physiological integrity of an individual. The underlying neurobiological substrates involved in these processes were substancially investigated through the use of animal models of stress. In this context, a crescent number of studies have used more naturalistic animal tests, such as the social defeat test. Regarding neurobiological substrates, it is known that the amygdala plays an important role in the modulation of defensive responses. This forebrain structure has several neurotransmitters and receptors with important implications in emotional states. In this context, the neuropeptide Corticotropin Releasing Factor (CRF) and its receptors, CRF1 and CRF2, have been recently investigated as an important modulatory system of defensive reactions to aversive situations. Activation CRF mechanisms in the amygdala has been postulated as a possible neurochemical substrate underlying the emotional disorders, especially anxiety disorders, induced by stress in humans. To study anxiety-related responses induced by stressors in animals, the elevated plus maze (EPM) test has been widely used. While previous studies have emphasized the role of CRF1 receptors in modulation of anxiety in rodents exposed to the EPM, the involvement of CRF2 receptors remains unclear. Few studies, however, have investigated the effects of CRF and CRF1 and CRF2 antagonists injected directly into the amygdala on the defensive responses in mice. In addition, several studies are needed to clarify the complex relationship between CRF neurotransmission of the amygdala in the etiology of anxiety disorders related to previous exposure to stress. This study investigated the role of CRF in the amygdala upon the defense reactions evaluated in the EPM in mice previously exposed to acute social defeat. Therefore, we carried out experiments to (i) characterize the effects of acute social defeat on behavior in the EPM and on the levels of plasma corticosterone; (ii) to investigate the effects of intraamygdala microinjection of CRF, CRF1 and CRF2 antagonists on the behavior of mice in the EPM and (iii) to investigate the effects of intra-amygdala microinjections of CRF1 and CRF2 antagonists on anxiety-related behaviors of mice pre-exposed to acute social defeat. Results showed that the exposure to acute social defeat stress produces anxiogenesis at short and long terms (i.e, assessed 5 min and 10 days after stress exposure), however short-term anxiety response is variable. Stress-short term effects are accompanied by increased plasma corticosterone levels. In addition, while intra-amygdala CRF increases anxiety, local injection of CRF1 (but not CRF2) receptor antagonists produced anxiolytic-like effects, suggesting a tonic role of CRF1 in the modulation of anxiety in mice exposed to the EPM. However, it was not possible to determine what is the role of CRF neurotransmission in the responses displayed by mice pre-exposed to social defeat and submitted to EPM.